Cross β amyloid assemblies as complex catalytic machinery. Issue 62 (19th July 2021) - Pal, Sumit; Goswami, Surashree; Das, Dibyendu
Abstract : Short peptide-based cross β amyloid assemblies can mimic advanced enzyme functions and possibly were the earliest protein folds. Abstract : How modern enzymes evolved as complex catalytic machineries to facilitate diverse chemical transformations is an open question for the emerging field of systems chemistry. Inspired by Nature's ingenuity in creating complex catalytic structures for exotic functions, short peptide-based cross β amyloid sequences have been shown to access intricate binding surfaces demonstrating the traits of extant enzymes and proteins. Based on their catalytic proficiencies reported recently, these amyloid assemblies have been argued as the earliest protein folds. Herein, we map out the recent progress made by our laboratory and other research groups that demonstrate the catalytic diversity of cross β amyloid assemblies. The important role of morphology and specific mutations in peptide sequences has been underpinned in this review. We have divided the feature article into different sections where examples from biology have been covered demonstrating the mechanism of extant biocatalysts and compared with recent works on cross β amyloid folds showing covalent catalysis, aldolase, hydrolase, peroxidase-like activities and complex cascade catalysis. Beyond equilibrium, we have extended our discussion towards transient catalytic amyloid phases mimicking the energy driven cytoskeleton polymerization. Finally, a future outlook has been provided on the way ahead for short peptide-based systems chemistry approaches that can lead to the development of robust catalytic networks with improved enzyme-like proficiencies and higher complexities. The discussed examples along with the rationale behind selecting specific amino acids sequence will benefit readers to design systems for achieving catalytic reactivity similar to natural complex enzymes.